Availability of data for monitoring noncommunicable disease risk factors in India - Magdalena Z Raban; Rakhi Dandona; Lalit Dandona (The World Health Organization, 2012)
OBJECTIVE: To examine the availability of data measuring noncommunicable disease (NCD) risk factor indicators from household surveys conducted in India from 2000 to 2009. METHODS: Questionnaires and publications used in household surveys were identified through internet and PubMed searches and examined to determine which core NCD risk factor indicators recommended by the World Health Organization (WHO) for NCD monitoring were being measured. Surveys with a sample size of 5000 or more were included to ensure a certain level of precision. The completeness of core indicator measurement and the geographical representativeness of the surveys were assessed. FINDINGS: Twenty six surveys met the inclusion criteria. Among the WHO-recommended core behavioural risk factor indicators, those monitoring tobacco use were measured completely in national and subnational surveys; those assessing dietary intake and physical inactivity were measured only in subnational surveys, and those assessing alcohol use were not measured at all. Among WHO-recommended core biological risk factors, only body mass index was measured in national and subnational surveys, whereas blood pressure, fasting blood glucose and blood cholesterol were measured only in subnational surveys. Due to the use of non-standard indicator definitions, measurement of core indicators in some of the national and subnational surveys was incomplete. CONCLUSION: The availability of data on core risk factor indicators to monitor the increasing burden of NCDs is inadequate in India. These indicators using standardized definitions should be included in the periodic national household health surveys to provide data at the national and disaggregated levels.